Korelasi Penerapan Nilai-Nilai Pancasila dan Sikap Gotong Royong di Sekolah Dasar - Rr. Sherly Dwi Lestari; Akhwani Akhwani; M. Sukron Djazilan; Pance Mariati (Journal on Education, 2024)
This study aims to analyze the correlation between the application of Pancasila values and mutual cooperation among students at SDN Balas Klumprik 1 Surabaya. The subjects of this research were class IV students, totaling 83 students. This type of research uses quantitative descriptive using the correlation method. Data collection techniques using a questionnaire. The data were processed by researchers using the SPSS program. The data analysis used is pearson product moment correlation analysis. By testing the hypothesis t test, it can be concluded from the results of the research that the t count is 5.206 while the t table is 1.98969. The results of the study show that there is a significant correlation between the application of Pancasila values and mutual cooperation. The results obtained in the Pearson product moment correlation test were 0.466 which could be interpreted as being in the low or sufficient category. The form of the correlation is positive correlation, which means that the higher the application of Pancasila values, the higher the attitude of mutual cooperation.